Importance of creativity development for Commercial Engineering career students from the teaching-learning process - Piguave Pérez, Vicenta Rocío (2014)
The objective of this work is to place the importance of creativity development for students into university contexts, therefore a diagnosis of the issue is presented in the students who aspire to reach higher levels of personal development and emotional health in social environments increasingly complex and competitive, to the demands of the entrepreneurial sector towards professionals in order to solve in an original and independent way, the decision-making processes, products and innovative services generation that solve problems on the field as a way to improvetheir quality of life. This study was conducted with students from «Universidad Laica Eloy Alfarode Manabí» in the career of Commercial Engineering, through a survey and additionally interviews were conducted to professors to supplement the information gathered by the survey. The synthesis of the results and recommendations are presented for routing teaching tasks placing the professor as the main promoter ofcreativity from the learning process.